To the knowledge of the aphenopsoid Trechine beetles (Coleoptera: Carabidae: Trechini) of the Caucasus - I.A. Belousov (Кавказский энтомологический бюллетень, 2009)
Meganophthalmus medvedevi Belousov et Koval, sp. n. (Coleoptera: Carabidae: Trechini), is described from eastern Abkhazia (type locality Golova Otapa Cave). Surprisingly, the new species turned out to be more closely related to Meganophthalmus kravetzi Komarov, 1993 from Kabardino-Balkaria than to the geographically neighboring Meganophthalmus mirabilis Kurnakov, 1959. Indeed, the former two species share some taxonomically important characters: the posterior lateral seta of pronotum lacking, both the scutellary and the apical strioles reduced, and the elytral microsculpture well-developed, consisting of rather high, nearly isodiametric meshes. Meganophthalmus medvedevi sp. n. is readily distinguished from M. kravetzi by the smaller size, the paler color of the upper-side, the shape of pronotum with the lateral margins regularly arcuate anteriorly and deeply sinuate posteriorly, the pronotal hind angles acutangular and strongly produced outwards, and by the male genitalia: the median lobe of the aedeagus is smaller, slenderer, its lamella is more clearly defined in dorsal view. The new species is named after Professor G.S. Medvedev. A revised key to all known species of the genus is provided and their distribution is mapped. The genus Taniatrechus Belousov et Dolzhanski, 1994 is among the most specialized troglobitic aphenopsoid trechine beetles known so far from the Caucasus. Nonetheless, its true systematic position remained a mystery, mainly due to the fact that this monotypical genus was described after a single female specimen. The discovery of a male specimen of Taniatrechus setosus allowed the authors of the present papers to study the male-associated characters and to evaluate variation in some external features. The diagnosis of the genus was accordingly modified to incorporate new knowledge. Based on the supernumerary supraorbital and submental setae and two dilated segments of the male protarsi as well as on the male genitalic structure, the genus Taniatrechus has been suggested to be most closely related to the Balkan genus Pheggomisetes Knirsch, 1923 and, in a sense, to bridge the gap between the phyletic series of Pheggomisetes and that of Aphaenops [Jeannel, 1928]. This could be interpreted as an additional evidence for ancient communications between the West Caucasus and the Balkans.